Successful use of transarterial radioembolization with yttrium‐90 (TARE‐Y90) in two children with hepatoblastoma. Issue 9 (30th June 2020) - Aguado, Allison; Dunn, Stephen P.; Averill, Lauren W.; Chikwava, Kudakwashe R.; Gresh, Renee; Rabinowitz, Deborah; Katzenstein, Howard M.
Abstract: Primary malignant liver tumors are rare but all require surgical resection as part of therapy with curative intent. A minority of patients have resectable tumors at diagnosis. Chemotherapy has a therapeutic role in hepatoblastoma but only one‐third of patients have resectable disease at diagnosis. Two children with hepatoblastoma and suboptimal responses to initial chemotherapy received therapy with transarterial radioembolization utilizing yttrium‐90 (TARE‐Y90) and had significant response leading to resection and remission. The role of TARE‐Y90 needs to be studied further to define its use in primary pediatric liver neoplasms.